RANGKUMAN dan pengayaan matematika kelas III SD semester 2 / Erni Suswanti...[et.al]; editor, Y. Hery Kurniyanta, Nimas Palmasari, Erni Suswanti; Ilustrator, Harnawan - Erni Suswanti; Hery Kurniyanta, Y; Nimas Palmasari; Harnawan (Kanisius, 2016)
139 hlm. : ilus. ; 25 cm.